Rental value determination of temporary easement valuation for construction site - Goh, Ko Chian (2022)
In Malaysia, the easement valuation is less awareness part of real estate valuation. Easement valuation has become a big problem because there are only has vague compensation guidelines in literature and there are lack of guidelines and less discussion in Malaysia Valuation Standard (MVS) year 2019. The main focus of the valuation field in Malaysia is on the general real estate valuation such as residential, commercial, and agricultural land valuation. The real estate valuation system in Malaysia still imperfect as there are many things should be improved in the future especially for easement valuation. Thus, first objective in this research to identify the factors that influence rental value determination of temporary easement valuation for construction site, second objective is to assess challenges for the valuer in rental value determination of temporary easement for construction site and the third objective is to evaluate the role of mediators on the influential factors to rental value determination of temporary easement valuation. Quantitative approach was adopted in this study by conducting questionnaire with 38 participants from private and government sectors by using simple random sampling. Descriptive analysis including frequency analysis and mediation analysis was used to interpret the data. The findings showed that there is no mediation between location factor and rental value determination of temporary easement. The findings also showed that challenges of valuer fully mediate the relationship between others factors (physical attributes, condition of easement, economic and market condition) and rental value determination of temporary easement valuation. This research has resulted onto the landowner as the easement can help to protect the landowner’s rights on their own property